The application of food grade short chain fatty acids to prevent infestation of Tyrophagus putrescentiae on dry cured ham and the effects on sensory properties. (September 2020) - Rogers, William; Campbell, Yan L.; Zhang, Xue; Shao, Wenjie; White, Shecoya; Phillips, Thomas W.; Schilling, M. Wes
Abstract: Tyrophagus putrescentiae (ham mite) is difficult for commercial dry cured ham producers to control. Methyl bromide is an effective fumigant but is now banned as an ozone depleting substance, meaning alternative methods to control mite infestation must be found. This research was conducted to test the efficacy of C8 C9 C10 fatty acids combined with and without food grade coatings to control mite infestations on dry cured hams. Ham cubes were coated directly or wrapped in nets saturated with C8 C9 C10 with combinations of either soybean oil, xanthan gum (XG) or carrageenan (CG) + propylene glycol alginate (PGA). Cubes were then inoculated with 20 large mixed sex ham mites and stored for 14 days at 22 ± 2 °C and 70 ± 5% relative humidity. The soybean oil alone or in combination with 10% C8 C9 C10 in direct coating, and 1% and 10% C8 C9 C10 in coated nets controlled mite population growth. In addition, the use of 10% C8 C9 C10 + XG and 10% C8 C9 C10 + CG + PGA in direct coatings or in saturated nets, and 1% C8 C9 C10 + XG in saturated nets also inhibited mite population growth. Unexpectedly, the soybean oil solvent by itself effectively controlled mite population growth as well. Sensory evaluation was performed using a difference from control test (n = 8) and indicated that only 10% C8 C9 C10 mixed with soybean oil and 100% soybean oil did not impart sensory differences to ham when used as a coating. However, for ham slices treated in saturated nets and gum with C8 C9 C10 mixtures in either coating or saturated nets did impart sensory differences. Results indicated that C8 C9 C10 and soybean oil could be used in coating formulations to control ham mites but long-term testing, sensory evaluation, and scaled up testing is needed prior to industrial implementation. Highlights: C8 C9 C10 (10%) controlled mite population growth, but imparted sensory differences. Soybean oil (100%) controlled mite growth. Soybean oil was an effective solvent for delivering C8 C9 C10 .